Paradiplomacy Pemerintah Kota Bandung Melalui Kerja Sama Sister City - Gilang Nur Alam; Arfin Sudirman (Jurnal Ilmiah Hubungan Internasional, 2020)
Various forms of international cooperation that have been carried out by the Bandung City include receipt of grant funds, short-term investments, infrastructure assistance, youth exchanges, scholarships, and cultural cooperation. The paradigm forms other than consisting of investment searches also consist of sister cities, the establishment of joint projects, and various forms of delegation delivery carried out between subnational actors. The position of this study seeks to examine the involvement of city governments, especially Bandung City in carrying out their foreign relations, which then focuses on understanding how the sister city concept that has been widely practiced in various countries can be seen through the paradigm approach in Indonesia. The paradigm of Bandung City in the form of a sister city with its city partners has resulted in several benefits as well as opportunities to improve the welfare of the city community while participating in national development especially in developing Indonesian diplomacy.